If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -9 = -7 + 5 Reorder the terms: -9 + x = -7 + 5 Combine like terms: -7 + 5 = -2 -9 + x = -2 Solving -9 + x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = -2 + 9 Combine like terms: -9 + 9 = 0 0 + x = -2 + 9 x = -2 + 9 Combine like terms: -2 + 9 = 7 x = 7 Simplifying x = 7
| 4n-n=-12 | | x-9/3=5 | | x^4-5x^2-50=0 | | 3-5(2x-1)+1x=-10 | | 7(7y+2)-9=-2 | | -5y-9=-y+1 | | 6(c+4c)=4c-18 | | 6x+4(4x-15)=50 | | -2=w/5 | | 3k-9=7+2k-k | | -4x+4(2x+8)=-8+8(x+8) | | L+50=1.32 | | -8/9(9+y)=64 | | 5/3x+1/3x=8/3+8/3x | | -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 |